In search of organizational crime in the U.S.: the FCPA court records - Fürstenberg, Alexander; Klinkhammer, Julian (Organizational crime, 2023)
Due to the Foreign Corrupt Practices Act (FCPA), anti-corruption enforcement has gained importance nationally and internationally—especially in corporate prosecutions. Subsequently, we first ask how the enforcement process has evolved since FCPA prosecutions began; second, what organizational structures support the organizational embedding of corruption; and third, what is the empirical relevance of organizational corruption in the US. Using a full survey of FCPA cases between 1977 and 2018, we show that the number of filed cases is systematically connected with the type of procedural conclusions and its sanctioning. Using case studies, we qualitatively illustrate the embeddedness of corrupt structures in firms and descriptively demonstrate, based on the aforementioned FCPA full survey that organizationally embedded corruption as a distinct form is similarly prevalent as corruption committed by individuals for personal gain.
Gesehen am 19.06.2023